2016
DOI: 10.1016/j.ijheatmasstransfer.2016.03.079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surfactant on stability and thermo-physical properties of metal oxide nanofluids

Abstract: Optimal thermo-physical properties of nanofluids provide an opportunity to overcome energy associated difficulties, in addition to providing new alternatives to catch, store and exchange of energy. A significant reduction in energy consumption is possible by improving the performance of a heat exchanger circuit, and may in part alleviate current energy related challenging issues such as global warming, climate change, and the fuel crisis. The objective of this work is to gain an insight into the overall stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
82
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(89 citation statements)
references
References 31 publications
2
82
0
5
Order By: Relevance
“…Nanofluids are synthesized by suspending nanoparticles which may be metallic (Al, Cu, Al 2 O 3 , SiC, AlN, SiN) or non-metallic (graphite, carbon nanotubes) in base fluids. Applications of nanofluids are growing in increasingly rich and diverse technologies including anti-bacterial systems, cancer therapy, solar cell enhancement and coolants for propulsion and lubrication designs [2][3][4][5]. Nanofluid convective heat transfer and other thermal characteristics have been recently reviewed by Tripathi and Bég [6] for application in pharmacology, Kleinstreuer and Xu [7] for microchannels, Sadeghi et al [8] for circular tubes fitted with helical inserts, Vajjha et al [9] for turbulent flows, Shin and Banerjee [10] for nano-materials processing, Huminic and Huminic [11] for curve tube and Mahian et al [12] for entropy generation minimization.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluids are synthesized by suspending nanoparticles which may be metallic (Al, Cu, Al 2 O 3 , SiC, AlN, SiN) or non-metallic (graphite, carbon nanotubes) in base fluids. Applications of nanofluids are growing in increasingly rich and diverse technologies including anti-bacterial systems, cancer therapy, solar cell enhancement and coolants for propulsion and lubrication designs [2][3][4][5]. Nanofluid convective heat transfer and other thermal characteristics have been recently reviewed by Tripathi and Bég [6] for application in pharmacology, Kleinstreuer and Xu [7] for microchannels, Sadeghi et al [8] for circular tubes fitted with helical inserts, Vajjha et al [9] for turbulent flows, Shin and Banerjee [10] for nano-materials processing, Huminic and Huminic [11] for curve tube and Mahian et al [12] for entropy generation minimization.…”
Section: Introductionmentioning
confidence: 99%
“…A strong relationship exists between nanofluids thermal conductivity and various parameters, namely: nanoparticle volume fraction, particle material, size and shape, base fluid material and temperature, specific heat capacity, type of surfactant, and density …”
Section: Introductionmentioning
confidence: 99%
“…Also the pH has an effect on the nanofluids thermal conductivity as its enhancement ratio increases with acidity . Furthermore, the thermal conductivity enhancement ratio can be affected by surfactants and additives used to prevent particle agglomeration . A summary of experimental studies on nanofluids thermal conductivity can be found in Rashmi et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanofluids usually exhibit high thermal conductivities, which are significant to the development of energy, and have been widely used in drug delivery solar cells, lipase immobilization, soil remediation, lubrication, and hydraulic fracturing of gas and oil. In addition, nanofluids have been introduced to the enhanced oil recovery (EOR) area due to their unique thermal properties and large surface area [4][5][6][7][8]. Many works have been done to study the EOR performance of nanofluids composed of different nanoparticles.…”
mentioning
confidence: 99%